Field Reporting on the Working of Social Welfare Schemes - Planning Commission (Planning Commission, 1970)
While studying organisational structures of development offices in districts under a detailed study of "Development Staff at the District and Lower Levels" conducted in 1968, wide disparities in organisational structures, overlapping functions in respect of issuing loans and grants and uncoordinated implementation of programmes in social services sector were noticed. It was, therefore felt that a further probe of sane of the important programmes could be undertaken, the working of social welfare programmes being one of them. The present study was therefore token up under the organisation's programme of periodical field reporting other than its regular programme of intensive depth studies. The field work of the study was initiated in September, 1969 and was completed in May, 1970. The purpose of this study was to take a census of the multiplicity of departments and autonomous agencies that were covering multifarious social welfare activities for socially and physically handicapped and under-privileged sections of the society. This survey covered all the 38 districts where the PED offices were located.
Programme Evaluation Organisation Planning Commission Government of India